Association between a soy-based infant diet and the onset of puberty: A systematic review and meta-analysis - Oliveira, Flávia Ramos Kazan [UNESP]; Gustavo, Ana Flora Silva E. [UNESP]; Goncalves, Renan Braga [UNESP]; Bolfi, Fernanda [UNESP]; Mendes, Adriana Lúcia [UNESP]; Nogueira, Vania dos Santos Nunes [UNESP] (Public Library of Science (PLoS), 2021)
The objective of this systematic review was to evaluate the association between a soybased infant diet and the onset of puberty. We included studies in which children were fed a soy-based diet, and we compared them with those who were not. The primary outcomes were the onset of puberty in girls (thelarche, pubarche, and menarche age), boys (pubarche, voice change, testicular and penis enlargement age), and both (risk of delayed and precocious puberty [PP]). Search strategies were performed in PubMed, Embase, LILACS, and CENTRAL databases. Two reviewers selected eligible studies, assessed the risk of bias, and extracted data from the included studies. The odds ratio (OR) and mean difference (MD) were calculated with a 95% confidence interval (CI) as a measure of the association between soy consumption and outcomes. We used a random-effects model to pool results across studies and the Grading of Recommendations Assessment, Development, and Evaluation to evaluate the certainty of evidence. We included eight studies in which 598 children consumed a soy-based diet but 2957 did not. The primary outcomes that could be plotted in the meta-analysis were the risk of PP and age at menarche. There was no statistical difference between groups for PP (OR: 0.51, 95% CI: 0.09 to 2.94, 3 studies, 206 participants, low certainty of evidence). No between-group difference was observed in menarche age (MD 0.14 years, 95% CI -0.16 to 0.45, 3 studies, 605 children, low certainty of evidence). One study presented this outcome in terms of median and interquartile range, and although the onset of menarche was marginally increased in girls who received a soy-based diet, the reported age was within the normal age range for menarche. We did not find any association between a soy-based infant diet and the onset of puberty in boys or girls.